Theoretical views on "Term", "Terminology" and "Terminological Field" in Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In linguistics, there are concepts of “term”, “terminology” and “terminological field", and we can see that scientists have advanced different opinions and views about these concepts. Having studied and analyzed these opinions and views, we have outlined our thoughts in this article.